Peptide‐functionalized starPEG/heparin hydrogels direct mitogenicity, cell morphology and cartilage matrix distribution in vitro and in vivo. (4th June 2017) - Hesse, Eliane; Freudenberg, Uwe; Niemietz, Thomas; Greth, Carina; Weisser, Melanie; Hagmann, Sébastien; Binner, Marcus; Werner, Carsten; Richter, Wiltrud
Abstract: Cell‐based tissue engineering is a promising approach for treating cartilage lesions, but available strategies still provide a distinct composition of the extracellular matrix and an inferior mechanical property compared to native cartilage. To achieve fully functional tissue replacement more rationally designed biomaterials may be needed, introducing bioactive molecules which modulate cell behavior and guide tissue regeneration. This study aimed at exploring the impact of cell‐instructive, adhesion‐binding (GCWGGRGDSP called RGD) and collagen‐binding (CKLER/CWYRGRL) peptides, incorporated in a tunable, matrixmetalloprotease (MMP)‐responsive multi‐arm poly(ethylene glycol) (starPEG)/heparin hydrogel on cartilage regeneration parameters in vitro and in vivo . MMP‐responsive‐starPEG‐conjugates with cysteine termini and heparin‐maleimide, optionally pre‐functionalized with RGD, CKLER, CWYRGRL or control peptides, were cross‐linked by Michael type addition to embed and grow mesenchymal stromal cells (MSC) or chondrocytes. While starPEG/heparin‐hydrogel strongly supported chondrogenesis of MSC according to COL2A1, BGN and ACAN induction, MMP‐degradability enhanced cell viability and proliferation. RGD‐modification of the gels promoted cell spreading with intense cell network formation without negative effects on chondrogenesis. However, CKLER and CWYRGRL were unable to enhance the collagen content of constructs . RGD‐modification allowed more even collagen type II distribution by chondrocytes throughout the MMP‐responsive constructs, especially in vivo . Collectively, peptide‐instruction via heparin‐enriched MMP‐degradable starPEG allowed adjustment of self‐renewal, cell morphology and cartilage matrix distribution in order to guide MSC and chondrocyte‐based cartilage regeneration towards an improved outcome. Copyright © 2017 John Wiley & Sons, Ltd.